Effect of different post-space pretreatments on fiber post bonding to root dentine - Homayon Alaghemand; Mansoreh Mirzae; Elham Ahmadi; Akam Saidi (Wolters Kluwer Medknow Publications, 2013)
Background: Before the resin bond endodontic post-cementation, various solutions are used to improve bond strength of these posts to root dentine. The purpose of this study was to evaluate the effect of the different pre-treatments (ethanol, ethylene de amine tetra acetic acid [EDTA] and EDTA + ethanol) on the bond strength of adhesively lutted tooth colored fiber post. Materials and Methods: Forty-eight human anterior teeth (incisor and canine) were selected in this experimental study. The species were endodontically treated, and the post-space was prepared. The species were randomly divided into four groups of 12 teeth in each and were treated as follows: (i) 0.1 M EDTA, (ii) 99.6% ethanol, (iii) 0.1 M EDTA followed by 99.6% ethanol and (iv) without any treatment (control). A push-out test was carried out after 24 h. Each tooth was cut into three 1 mm-thick sections. Fracture type was assessed using stereomicroscope. The data were analyzed by one way-ANOVA followed by Scheffe post-hoc test at P = 0.05. Results: Almost, in EDTA and (EDTA + ethanol) every sample failed at the interface between post and lutting cement. Predominant failure mode in ethanol and control group was mixed failure. The surface treatment methods did not have any significant effect (P > 0.05) on any group but EDTA group had the highest bond strength. Conclusion: Surface treatment with (ethanol, EDTA, and EDTA + ethanol) does not significantly appear to be effective in improving the bond strength of fiber posts into root dentine. The highest bond strength was observed in EDTA group and the lowest in the control group.